Balance between Cytosolic and Chloroplast Translation Affects Leaf Variegation. Issue 1 (15th November 2017) - Wang, Ruijuan; Zhao, Jun; Jia, Min; Xu, Ni; Liang, Shuang; Shao, Jingxia; Qi, Yafei; Liu, Xiayan; An, Lijun; Yu, Fei
Abstract : Mutations in cytosolic ribosomal protein RPS21 enhance leaf variegation in Arabidopsis by loss of chloroplast VAR2/AtFtsH2 protein, an effect dependent on chloroplast translation. Abstract: The development of functional chloroplasts relies on the fine coordination of expressions of both nuclear and chloroplast genomes. We have been using the Arabidopsis ( Arabidopsis thaliana ) yellow variegated ( var2 ) leaf variegation mutant as a tool to dissect the regulation of chloroplast development. In this work, we screened for var2 genetic enhancer modifiers termed enhancer of variegation ( evr ) mutants and report the characterization of the first EVR locus, EVR1 . We showed that EVR1 encodes the cytosolic 80S ribosome 40S small subunit protein RPS21B and the loss of EVR1 causes the enhancement of var2 leaf variegation. We further demonstrated that combined S21 activities from EVR1 and its close homolog, EVR1L1, are essential for Arabidopsis, and they act redundantly in regulating leaf development and var2 leaf variegation. Moreover, using additional cytosolic ribosomal protein mutants, we showed that although mutations in cytosolic ribosomal proteins all enhance var2 leaf variegation to varying degrees, the 40S subunit appears to have a more profound role over the 60S subunit in regulating VAR2-mediated chloroplast development. Comprehensive genetic analyses with var2 suppressors that are defective in chloroplast translation established that the enhancement of var2 leaf variegation by cytosolic ribosomal protein mutants is dependent on chloroplast translation. Based on our data, we propose a model that incorporates the suppression and enhancement of var2 leaf variegation, and hypothesize that VAR2/AtFtsH2 may be intimately involved in the balancing of cytosolic and chloroplast translation programs during chloroplast biogenesis.